Use of Information Technology in Physical Education Lesson - Alina Petruta Turcanu (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The use of new technologies in physical education requires teachers to have a set of knowledge and skills that would favor the use and capitalization of new technologies in the didactic activity. These modern technologies, used in the physical education lesson, represent one of the most complex forms of integration of informal education into formal education. Contributing to the efficiency of the researched study, the use of these information technologies in the teaching-learning-evaluation process achieves the diversification of didactic strategies, allowing the student access to various structured information, presented in different ways of visualization. Technology has enough potential to simplify effective physical education instruction and provide teachers with key information. In this study, I aimed to use information technology in physical education classes to increase the performance of learning sports skills in physical activities among primary school students, respectively the 4th grade.